Sarcomatoid carcinoma in cytology: Report of a rare entity presenting in pleural and pericardial fluid preparations. Issue 8 (25th March 2019) - Basu, Atreyee; Moreira, Andre L.; Simms, Anthony; Brandler, Tamar C.
Abstract : Sarcomatoid carcinoma is rarely found in pleural or pericardial fluid, with very few cases published to date. Here, we describe a 59‐year‐old female who presented with cough persisting for 5 months. Chest CT scan revealed a 6.0 cm cavitary mass in the left lung base with bulky mediastinal and hilar lymphadenopathy. An additional 1.2 cm right adrenal mass was seen and was suspicious for metastatic disease. The patient developed dyspnea, tachycardia, pleuritic chest pain and generalized weakness and was admitted to the hospital. She was found to have pleural and pericardial effusions, which were drained and sent to cytology. The fluid revealed enlarged highly pleomorphic malignant cells, some displaying multinucleation with irregular nuclear borders, coarse chromatin and prominent nucleoli. Tumor cells were positive for CK7 and Vimentin and negative for MOC‐31, Ber‐EP4, B72.3, Sox10, Melan‐A, TTF‐1, Napsin‐A and CK20. A concurrent surgical biopsy of the tumor mass displayed immunopositivity for AE1/AE3 and CAM5.2. The tumor was negative for p40, TTF‐1, calretinin, D2‐40 and STAT6. A diagnosis of sarcomatoid carcinoma with giant cells and spindle cells was rendered. Sarcomatoid carcinomas of the lung are very uncommon consisting of 1% of non‐small‐cell lung carcinomas and are even more unusual in cytology specimens. Despite its rarity, it is important to keep this entity in mind in the differential diagnosis of a fluid specimen with bizarre nuclear atypia and the above staining pattern.